Glucagon-Like Peptide-1 Receptor Agonists and Cardiovascular Events: A Meta-Analysis of Randomized Clinical Trials. (3rd March 2011) - Monami, Matteo; Cremasco, Francesco; Lamanna, Caterina; Colombi, Claudia; Desideri, Carla Maria; Iacomelli, Iacopo; Marchionni, Niccolò; Mannucci, Edoardo
Abstract : Objective . Data from randomized clinical trials with metabolic outcomes can be used to address concerns about potential issues of cardiovascular safety for newer drugs for type 2 diabetes. This meta-analysis was designed to assess cardiovascular safety of GLP-1 receptor agonists. Design and Methods . MEDLINE, Embase, and Cochrane databases were searched for randomized trials of GLP-1 receptor agonists (versus placebo or other comparators) with a duration ≥12 weeks, performed in type 2 diabetic patients. Mantel-Haenszel odds ratio with 95% confidence interval (MH-OR) was calculated for major cardiovascular events (MACE), on an intention-to-treat basis, excluding trials with zero events. Results . Out of 36 trials, 20 reported at least one MACE. The MH-OR for all GLP-1 receptor agonists was 0.74 (0.50–1.08), P = .12 (0.85 (0.50–1.45), P = .55, and 0.69 (0.40–1.22), P = .20, for exenatide and liraglutide, resp.). Corresponding figures for placebo-controlled and active comparator studies were 0.46 (0.25–0.83), P = .009, and 1.05 (0.63–1.76), P = .84, respectively. Conclusions . To date, results of randomized trials do not suggest any detrimental effect of GLP-1 receptor agonists on cardiovascular events. Specifically designed longer-term trials are needed to verify the possibility of a beneficial effect.